2005
DOI: 10.2174/1573402052952762
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotection with Anti-Hypertensives: Reduction of Proteinuria and Improvement of Oxygenation via Inhibition of the Renin-Angiotensin System

Abstract: Hypertension is a common cause of chronic kidney disease (CKD) and even more common sequelae of CKD. While strict control of blood pressure is essential to preserve residual renal function, numerous clinical trials have demonstrated that inhibitors of the renin-angiotensin system (RAS), i.e. angiontensin converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARB), reduce the progression of CKD. These studies have examined type I and type II diabetic as well as non-diabetic nephropathies, utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 109 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Experimental and clinical data have shown that Renin-Angiotensin System (RAS) is clearly involved in the pathogenesis of renal diseases (2,3). Acting on angiotensinergic type 1 (AT 1 ) receptors, Angiotensin (Ang) II induces progressive kidney injury via multiple mechanisms, including intraglomerular hypertension, sodium and water retention, stimulation of fibrogenic mediators, enhanced free radical formation, and contraction of mesangial cells (3,4). Moreover, clinical trials have demonstrated that RAS inhibitors, angiotensin-converting enzyme inhibitors (ACEi) and AT 1 receptor blockers reduce the rate of progression of CRF to ESRD (5,6).…”
Section: Hronic Renal Failure (Crf) In Childhood Frequently Resultsmentioning
confidence: 99%
“…Experimental and clinical data have shown that Renin-Angiotensin System (RAS) is clearly involved in the pathogenesis of renal diseases (2,3). Acting on angiotensinergic type 1 (AT 1 ) receptors, Angiotensin (Ang) II induces progressive kidney injury via multiple mechanisms, including intraglomerular hypertension, sodium and water retention, stimulation of fibrogenic mediators, enhanced free radical formation, and contraction of mesangial cells (3,4). Moreover, clinical trials have demonstrated that RAS inhibitors, angiotensin-converting enzyme inhibitors (ACEi) and AT 1 receptor blockers reduce the rate of progression of CRF to ESRD (5,6).…”
Section: Hronic Renal Failure (Crf) In Childhood Frequently Resultsmentioning
confidence: 99%
“…A large number of prospective, randomized, controlled studies have demonstrated the beneficial effects of angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs). These studies are covered in detail in our previous overview but, taken together, they ascribe the profound beneficial effects of blockade of RAS to reno-protection that goes beyond mere BP reduction (11). In particular, Weinberg et al reported that the BP-lowering effects of an ARB, candesartan cilexetil (approved dosage range in Japan up to 12 mg/day), reached a plateau when doses were increased to 96 mg/day.…”
Section: Blockade Of the Renin-angiotensinmentioning
confidence: 99%
“…Although HIF stimulation holds promise as a future therapy, at present the best modality for the treatment of kidney disease is blockade of the RAS (11). One important mechanism of the BP-independent renoprotective effect of this blockade is the preservation of peritubular capillary perfusion.…”
Section: Angiotensin Blockade As a Therapeutic Modality Against Renalmentioning
confidence: 99%
“…Ang II constricts precapillary arterioles, leading to increased blood pressure, and also promotes renal sodium retention, which, in turn, causes expansion of circulating volume [22,23]. However, if this alteration is sustained, it will probably cause glomerular injury and an accelerated loss of kidney function over time [79]. At renal site, the locally produced Ang II constricts the efferent more than the afferent arteriole [22,23,81].…”
Section: Renin Angiotensin Systemmentioning
confidence: 99%